2019
DOI: 10.21873/anticanres.13249
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment Outcomes of Adult Patients With Rhabdomyosarcoma After Multimodality Treatment

Abstract: Background: Adults with rhabdomyosarcoma (RMS) have a worse clinical outcome compared to pediatric cases. In the present study, the failure pattern and clinical outcome of adult patients with RMS who received multimodality treatment at our Institution was assessed. Patients and Methods: Data were retrospectively recorded and analyzed from 20 adult patients, aged 19 years or more, who were treated for RMS at our Institution between 2004 and 2015. Disease-free (DFS) and overall (OS) survival after starting treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…In our analysis, anatomical location divided into “favourable” and “unfavourable” failed to reach statistical significance; this was also the case in a study by Hawkins et al [ 1 ]. Nevertheless, the primary tumour location is still clinically meaningful, as tumours occurring in, for example, the retroperitoneum, can become quite large before producing signs and symptoms [ 22 ]. The reason for the low percentage of patients receiving chemotherapy in our study (54%) ( Table 5 ) could be the predominance of pleomorphic subtype in our cohort (44%), as the majority of this subgroup would be treated as nonrhabdomyosarcoma with surgery only or with a combination of radiotherapy, as pleomorphic rhabdomyosarcoma has been shown not to be as responsive to chemotherapy as the embryonal or alveolar subtypes [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, anatomical location divided into “favourable” and “unfavourable” failed to reach statistical significance; this was also the case in a study by Hawkins et al [ 1 ]. Nevertheless, the primary tumour location is still clinically meaningful, as tumours occurring in, for example, the retroperitoneum, can become quite large before producing signs and symptoms [ 22 ]. The reason for the low percentage of patients receiving chemotherapy in our study (54%) ( Table 5 ) could be the predominance of pleomorphic subtype in our cohort (44%), as the majority of this subgroup would be treated as nonrhabdomyosarcoma with surgery only or with a combination of radiotherapy, as pleomorphic rhabdomyosarcoma has been shown not to be as responsive to chemotherapy as the embryonal or alveolar subtypes [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials have recently shown that long‐term maintenance therapy with relatively low‐dose chemotherapy provided longer survival in pediatric RMS cases . There are retrospective data indicating that long‐term treatments are related to the long survival of adult RMS patients, and thus long‐term low‐dose chemotherapy might be promising as a new strategy for adult RMS patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…RMS grows rapidly, has a high degree of malignancy, and is sensitive to chemotherapy and radiotherapy, but the effect of single treatment is poor; therefore, comprehensive treatment such as surgery, chemotherapy and radiotherapy are needed. 6 , 7…”
Section: Introductionmentioning
confidence: 99%